2016
DOI: 10.4103/0973-029x.185923
|View full text |Cite
|
Sign up to set email alerts
|

Epithelioid osteoblastoma of maxilla: A rare and aggressive variant of a benign neoplasm at an uncommon site

Abstract: Osteoblastoma (OB) is an uncommon benign bone-forming tumor accounting for <1% of all bone neoplasms. Unlike conventional OB, its small subset variant “Epithelioid osteoblastoma (EO)” is characterized by its propensity for local invasion and recurrent behavior. This rare variant of an uncommon tumor when occurs in an atypical site can lead to diagnostic problems more so due to ambiguous clinico-radiologic presentation. This was what faced in the present case of 18-year-old female with a swelling in upper jaw. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
15
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(15 citation statements)
references
References 9 publications
0
15
0
Order By: Relevance
“…14 Few cases have been reported in the jaws, with the mandible more frequently affected than the maxilla. 5,10,[14][15][16][17][18][19] In our series, 4 tumors (67%) affected the mandible, and only 2 (33%) affected the maxilla. Upon review of the literature, we found some reports of epithelioid/aggressive osteoblastomas showing microscopic features similar to our cases.…”
Section: Discussionmentioning
confidence: 47%
See 4 more Smart Citations
“…14 Few cases have been reported in the jaws, with the mandible more frequently affected than the maxilla. 5,10,[14][15][16][17][18][19] In our series, 4 tumors (67%) affected the mandible, and only 2 (33%) affected the maxilla. Upon review of the literature, we found some reports of epithelioid/aggressive osteoblastomas showing microscopic features similar to our cases.…”
Section: Discussionmentioning
confidence: 47%
“…Variable levels of mineralization and different stages of maturation of the calcified component were present, and peripheral maturation of "blue bone" to trabeculae of woven bone was a frequent finding. 18,19 Two of our cases showed a different concentric pattern of the mineralized component, resembling the so-called Liesegang rings. Osteoclastlike multinucleate giant cells, which have been frequently reported, 15,18,19 were observed occasionally in our cases.…”
Section: Discussionmentioning
confidence: 61%
See 3 more Smart Citations